Extension action in the face of the SARS-CoV-2 pandemic: The role of the UFV-CRP Molecular Diagnostics Laboratory and university protagonism - Evangelista Visôtto, Liliane; Medeiros Santana, Luanda; Frehner Kavalco, Karine; Pasa, Rubens; Vieira Good God, Pedro Ivo (Guará Journal, 2023)
With the health crisis established in early 2020, members of the academic community of the Federal University of Viçosa - Cam-pus Rio Paranaíba (UFV-CRP) proposed the creation of a SARS–CoV-2 diagnostic laboratory, by RT-qPCR. The purpose of this article is to report how the joint effort between the university, public and private institutions successfully promoted the installation of a testing laboratory on a new campus, outside the university headquarters, in the face of COVID-19. In almost two years of activity, the Molecular Diagnostics Laboratory (MDL) served 22 cities in the Alto Paranaíba/MG region and released 25,201 tests. In addition, MDL also trained undergraduate and graduate students in molecular diagnostic techniques for the coronavirus, acted in the fight against the spread of false in-formation on social networks and the spread of COVID-19 prophylactic methods. The installation of MDL provided the creation of a theoretical and practical discipline about the disease, and strengthened research on campus, allowing scientific ini-tiation projects related to COVID-19 to be carried out, with re-sults published in internationally indexed scientific journals.